PROTEROZOIC GRANITE-GNEISS MONOCLINES OF THE UKRAINIAN SHIELD AND THEIR MORPHOSTRUCTURAL TYPES - SHEVCHUK, V.; SHEVCHUK, Vol. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Allocation of granite-gneiss monoclines as special structural forms is argued. They are distributed in tectonic-magmatic regions. Classification of such structures is offered on the bases of structural-textural elements and their paragenesis reflecting the evolution of dynamic-kinematics conditions of the formation. It was done on the example of granite-gneiss monoclines of the Ukrainian Shield.